Free available chlorine initiated Baeyer–Villiger oxidation: A key mechanism for chloroform formation during aqueous chlorination of benzophenone UV filters. (1st January 2021) - Zhang, Xinyi; Wei, Dongbin; Sun, Xuefeng; Bai, Chenzhong; Du, Yuguo
Abstract: Chloroform, a regulated disinfection by-product in water, is often generated during chlorination disinfection treatment. However, the formation of chloroform is heavily dependent on the molecular structures of precursors. Moreover, compounds containing ketone moiety are ubiquitous in water environments. However, it is unclear if they can generate chloroform during chlorination. In this study, 14 benzophenones (BPs), efficient and widely used UV filters, with different substituents were selected to explore chloroform formation during chlorination. All 14 BPs generated chloroform, with yields dependent on their molecular structures and operational conditions. Compounds 2, 2′, 4, 4′-tetrahydroxy-BP and benzophenone produced the highest and lowest chloroform of 0.313 and 0.013 g/g, respectively, corresponding to the fastest and slowest formation rate constants of 1.41 × 10 −1 and 2.71 × 10 −2 min −1 . Alkaline conditions and high chlorine dosages were favorable to chloroform formation. Three reactions played key roles in chloroform formation from BPs: (1) chlorine initiated Baeyer–Villiger oxidation converted ketone moieties of BP molecules into esters; (2) the esters further underwent hydrolysis and formed phenolic and benzoic products; and (3) benzoic acids underwent decarboxylation and hydrolysis to form phenolic products. Subsequently, these phenolic products could further generate chloroform in the chlorination system. More importantly, BPs could generate chloroform in the ambient water matrices during practical chlorination treatment. This work emphasized the critical role of Baeyer–Villiger oxidation for chloroform formation, implying that pollutants containing aromatic ketone moieties generate chloroform during chlorination disinfection, and their potential risk should therefore be reviewed. Graphical abstract: Image 1 Highlights: Chlorination treatment on benzophenones (BPs) would produce chloroform. BPs produced chloroform via Baeyer–Villiger oxidation, hydrolysis, decarboxylation. BPs containing meta-hydroxyl groups could rapidly generate more chloroform. Alkaline condition and high FAC dosage were beneficial for chloroform formation. Abstract : Baeyer–Villiger oxidation was a key mechanism for chloroform formation from pollutants containing aromatic ketone moieties during chlorination disinfection.